La violencia vicaria considerada como agravante del delito de violencia psicológica contra la mujer o miembros del núcleo familiar - Maza Cango., Lizbeth Dayana (2024)
The present Curricular Integration Work entitled "Vicarious violence considered as an aggravating factor in the crime of psychological violence against women or family members" has been undertaken to address the persistent issue of violence against women in our society because women continue to be victims of various forms of violence, often perpetrated by their partners, with far-reaching consequences not only for the women themselves but also for their children and other members of the family nucleus. However, this work specifically focuses on the psychological violence faced by women, defined as any aggressive behavior occurring between individuals without involving physical contact or aggression. This type of violence, whether executed by an individual or a group, manifests verbally through actions such as disqualifications, humiliations, and belittlement. Such behaviors have detrimental emotional effects on the victim and can manifest in various societal realms, including the family, school, social, and workplace environments. In addition to the psychological violence prevalent in the living and developmental environments of women, another form of violence—vicarious violence—is introduced. This emerging type of gender-based violence occurs when the aggressor utilizes close family members, particularly children, as instruments of control, manipulation, or revenge against the mother. It is essential to note that vicarious violence extends beyond cases where the father is the aggressor, as it can manifest in other family relationships or contexts. Furthermore, it is imperative to recognize that vicarious violence is embedded within the broader context of gender-based violence, encompassing various forms of mistreatment and abuse directed at women based on their gender. The research employed the scientific method, incorporating inductive, deductive, analytical, synthetic, and statistical approaches. The study aimed to elucidate fundamental concepts that contribute to an understanding of the research topic and to propose viable solutions to the identified problem.